Strategi Pemasangan Radar Pantai Untuk Identifikasi Potensi Ancaman Laut di Wilayah Selatan Pulau Jawa - Provid Ariantoko; Pujo Widodo; Herlina Juri Risma Saragih; Panji Suwarno; Endro Legowo; Moch Yurianto (Universitas Trunojoyo Madura, 2023)
The conditions of vulnerability and potential security threats in the sea area of the southern part of Java Island and the level of ability of elements operating in the area are still inadequate both in quality and quantity. This thesis uses qualitative research methods. Some of the vulnerabilities that can occur include illegal fishing, smuggling, pollution at sea, illegal crossing, terrorism at sea, and people smuggling. These threats can endanger Indonesia's interests in many aspects such as defense and security, the economy, and territorial sovereignty. Therefore a plan is needed to conceptualize the installation of a coastal radar to improve security in the area. The IMSS (Integrated Maritime Surveillance System) radar, which is already operating in the Malacca Strait area as an empirical example, will develop the coastal radar concept in the southern region of Java Island. With the existence of a coastal radar in the area that functions as an early warning system, it is hoped that all forms of threats and violations can be anticipated very well. The addition of a security element in the sea area of the southern part of Java Island in the form of installing a coastal surveillance radar is very important to implement given that the level of capability of the security elements operating in the area is considered to be insufficient for security in the wider sea area.